THE CORRESPONDENCE OF THE TONGUE CENTRAL LINE DEVIATION WITH THE PATHOLOGY OF SPINAL CURVATURE - M.A. Shundryk; I.Y. Marchenko; I.M. Tkachenko; Y.Y. Vodoriz; V.V. Boyko (Проблеми екології та медицини)
Scientific researches suggest posture problems as a factor affecting the occurrence of occlusion anomalies as well as their complications. The surface of the tongue may reflect disorders in digestion, cardiac activity, nervous and endocrine systems. In the literature, there is data that the tongue can help in the diagnosis of many diseases, because its general appearance is in a significant relation with its anatomical features. Receptors of its mucous membrane are closely related to the central nervous, cardiovascular, endocrine and locomotor systems. Aim. The purpose of the study was to determine the correspondence between the location of the tongue median line and the degree of distortion of the vertebral column at different levels in children with scoliosis. Materials and methods. Totally 56 children (30 girls, 26 boys) aged 11-14 years were examined, with a duration of musculoskeletal disorders 1-3 years. For each participant, the oral cavity examination was performed, the position of the middle line of the tongue was determined. X-ray images of vertebral column of patients from investigated groups were analyzed. Results. In the group with 1 year duration of the disease 25.02% patients had distorted median line of the tongue, in the group with 2 years of duration of the disease - 65,52% participants had the deviation of the medial line of the tongue, in the group with 3 years of duration of the disease 86.66% of patients had the deviation of the median line of the tongue. Conclusions. This research allows us to recommend paying attention not only to the size, color, state of the papillae of the tongue, but also to the position of the middle line, whose distortion may indicate the deviation of the vertebral column in different portions. Further research is needed to detect the mechanisms of influence of the spine and the influence of skeletal muscles on muscles of the maxillofacial area, which are involved in the formation of occlusion and function of the organs of the oral cavity.